(untitled) (International journal of artificial intelligence, 2026)
This article provides a scholarly analysis of the artistic-aesthetic and philosophical foundations of the poetics of Nodira’s poetry, a prominent female poet of classical Uzbek literature. The study reveals the unique interpretation of classical Uzbek literary traditions, Eastern poetic thinking, and Sufi concepts in Nodira’s works. Particular attention is paid to the poetess’s creative individuality, poetic mastery, and symbolic imagery within the framework of classical literature.